2017
DOI: 10.1136/bmj.j3808
|View full text |Cite
|
Sign up to set email alerts
|

Progress towards antimicrobial resistance containment and control in Indonesia

Abstract: A pilot programme to evaluate Indonesia’s antimicrobial resistance containment plan shows that progress is on the right track, but substantial strengthening is needed, say Harry Parathon and colleagues

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
71
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(78 citation statements)
references
References 17 publications
0
71
0
7
Order By: Relevance
“…Thus, the potentially high costs of reducing antimicrobial use may present a barrier to changing farmer behaviours. However, with increasing international pressure to address AMR there is a need to engage with both the private and public sectors; this is a strategic aim of the AMR action plan for Indonesia [24]. The process to achieve collaborative discussion between the public and private sectors on antimicrobial use in broilers has been initiated with meetings including both government representatives, broiler production companies, the pharmaceutical sector and other key stakeholders in poultry health on the subject of AMR [53].…”
Section: Economic Drivers Of Antimicrobial Usementioning
confidence: 99%
“…Thus, the potentially high costs of reducing antimicrobial use may present a barrier to changing farmer behaviours. However, with increasing international pressure to address AMR there is a need to engage with both the private and public sectors; this is a strategic aim of the AMR action plan for Indonesia [24]. The process to achieve collaborative discussion between the public and private sectors on antimicrobial use in broilers has been initiated with meetings including both government representatives, broiler production companies, the pharmaceutical sector and other key stakeholders in poultry health on the subject of AMR [53].…”
Section: Economic Drivers Of Antimicrobial Usementioning
confidence: 99%
“…Penilaian kesehatan bank sangat penting karena bank mengelola dana dari masyarakat yang dipercayakan kepada bank (Pramana & Artini, 2016). Kesehatan keuangan bank dianalisis dengan me-review data laporan keuangan, menghitung, membandingkan atau mengukur, menginterpretasikan dan memberi solusi (Parathon, Dzulkirom, & Farah, 2012) sehingga dapat diketahui kondisi kesehatannya akan memudahkan bank itu sendiri untuk memperbaiki kesehatannya (Permana, 2012). Penilaian kesehatan bank dapat dilihat dari berbagai aspek yang bertujuan untuk mengetahui dan menentukan apakah bank tersebut dalam kondisi yang sehat, cukup sehat, kurang sehat atau tidak sehat (Gandawari, Areros, & Keles, 2016).…”
Section: Pendahuluanunclassified
“…The results of the interview indicated that the respondent obtained it from unauthorized pharmacy. The availability of ethical drugs in unauthorized pharmacy and the free access of prescription drugs in some authorized pharmacies are still become issues that needs to be resolved in Indonesia [9,11,15]. Lack of control and weak policy enforcement toward access to drugs has triggered improper self-medication behavior.…”
Section: Discussionmentioning
confidence: 99%